Clathrin heavy chain, light chain interactions. - Winkler, F K (1983)
Purified pig brain clathrin can be reversibly dissociated and separated into heavy chain trimers and light chains in the presence of non-denaturing concentrations of the chaotrope thiocyanate. The isolated heavy chain trimers reassemble into regular polygonal cage structures in the absence of light chains. The light chain fraction can be further resolved into its two components L alpha and L beta which give different one-dimensional peptide maps. Radiolabelled light chains bind with high affinity (KD < 10(-10) M) to heavy chain trimers, to heavy chain cages and to a 110,000 mol. wt. tryptic fragment of the heavy chain. Both light chains compete with each other and with light chains from other sources for the same binding sites on heavy chains and c.d. spectroscopy shows that the two pig brain light chains possess very similar structures. We conclude that light chains from different sources, despite some heterogeneity, have a highly conserved, high affinity binding site on the heavy chain but are not essential for the formation of regular cage structures.